Exploring the Organometallic Route to Molecular Spin Qubits: The [CpTi(cot)] Case. (26th November 2020) - de Camargo, Luana C.; Briganti, Matteo; Santana, Francielli S.; Stinghen, Danilo; Ribeiro, Ronny R.; Nunes, Giovana G.; Soares, Jaísa F.; Salvadori, Enrico; Chiesa, Mario; Benci, Stefano; Torre, Renato; Sorace, Lorenzo; et al.
Abstract: The coherence time of the 17‐electron, mixed sandwich complex [CpTi(cot)], (η 8 ‐cyclooctatetraene)(η 5 ‐cyclopentadienyl)titanium, reaches 34 μs at 4.5 K in a frozen deuterated toluene solution. This is a remarkable coherence time for a highly protonated molecule. The intramolecular distances between the Ti and H atoms provide a good compromise between instantaneous and spin diffusion sources of decoherence. Ab initio calculations at the molecular and crystal packing levels reveal that the characteristic low‐energy ring rotations of the sandwich framework do not yield a too detrimental spin‐lattice relaxation because of their small spin–phonon coupling. The volatility of [CpTi(cot)] and the accessibility of the semi‐occupied, non‐bonding d z 2 orbital make this neutral compound an ideal candidate for single‐qubit addressing on surface and quantum sensing in combination with scanning probe microscopy. Abstract : The spin coherence of the sandwich complex [CpTi(cot)] survives for tens of μs at low temperature despite the presence of hydrogen atoms. This stems from its electronic structure and spin‐vibrational properties, investigated by ab initio calculations and terahertz spectroscopy. This evaporable molecule with d z 2 singly occupied orbital is a promising candidate for a coherent spin qubit and for single spin addressing.